Incidence of blindness in open-angle glaucoma in Sweden: a long-term follow-up study - Curt Ekström; Christoffer Carlsson (Upsala Journal of Medical Sciences)
Background: Open-angle glaucoma (OAG) is a leading cause of irreversible blindness. There are no prospective studies on the risk of developing blindness in both eyes in individuals with definite OAG. Methods: A total of 354 patients with newly diagnosed OAG, who had participated in four studies conducted at the Eye Department in Tierp, Sweden, from 1979 to 2006, were included in the investigation. Using the World Health Organization’s criteria for blindness, medical records, glaucoma case records, and visual fields were reviewed to identify patients who developed bilateral blindness. Incidence proportions and incidence rates were estimated. To assess potential risk factors for blindness, standardised morbidity ratios (SMRs) were calculated. The effects of age and sex were also analysed using Cox proportional hazard models. Results: By the end of the study in August 2023, 33 cases of blindness caused by OAG had been found, corresponding to an incidence proportion of 9.3% (95% confidence interval [CI]: 6.5–12.8%). Within the first 20 years, 29 cases were detected, yielding a proportion of 8.2% (95% CI: 5.5–11.6%). The incidence rate was estimated to be 8.6 per 1,000 person-years (95% CI: 5.9–12.6 per 1,000 person-years). Glaucoma-related blindness was associated with male sex (SMR 2.33; 95% CI: 1.13–4.80). The hazard ratio was doubled for every 5 year of increasing age (2.21; 95% CI: 1.60–3.05). Conclusion: In this study of blindness in newly diagnosed OAG in a Swedish population, approximately one in 10 patients progressed to bilateral blindness caused by the disease. Old age and male sex were identified as significant risk factors.